Analysis of ANBK-Based Literacy Skills and Digital Literacy Capability of Elementary School Students - Yulianita Kususma, Trifa; Cahyani, Isah (International Conference on Elementary Education, 2025)
Indonesia has always been a participant in the PISA assessment. From the PISA results, Indonesia still has a low ranking, with literacy or reading scores decreasing. In support of PISA, the government always makes improvements by carrying out National Assessments every year on a digital basis using computer devices. The results of this National Assessment can be obtained by each educational unit through the Education Report Card. This research aims to analyze the categories of literacy abilities of elementary school students in one of the ANBK-based West Bandung Regency and the Digital Literacy Skills of students in elementary schools. This ANBK-based literacy ability analysis was carried out by analyzing the school's Education Report Card and students' Digital Literacy Capabilities by analyzing five components, namely access, information, communication, creation and security. The research uses descriptive qualitative. This research uses literature studies, questionnaires and observations to obtain data. This research shows that school literacy is still in the medium category with an achievement of 70 and digital literacy skills with high access ability, accustomed to searching for information digitally, quite low use of communication, high digital creation, and low digital security. The results of the analysis show improvements that can be made based on the root of the problem, namely improving the quality of learning by using innovations in various appropriate learning models and implementing innovative literacy programs such as GLS, e-library, habituation.